Les avatars de la toponymie dans les confins géographiques, exemple du canal « Messier » en Patagonie chilienne - Frédéric Aitken; Jean-Numa Foulc; Pascal Mao; Nicolas Robinet (Confins)
This article focuses on toponymy in geographical confines through the example of the coastlines of the Chilean Patagonia and the Messier channel. It allows us to ask about the process that led to name this place in addressing at the same time their topogenesis, as the history of discovery, and the construction of the place and their onomastics as etymologies of the name, its evolution and subsequent uses. It is commonly accepted today that the channel is named in homage to the famous French astronomer Charles Messier. This article shows that the name has undergone various modifications during its appearances on different cartographic supports between the seventeenth and nineteenth century and would be originally from the Spanish term "Merced", which means "Grace". This demonstration shows the avatars which may affect the neotoponymy in these places.